AB1397-HPR CLINICAL FEATURES IN COHORT OF PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS IN KAZAKHSTAN. (June 2019) - Issayeva, Bakytsholpan; Saparbayeva, Maira; Kayyrgali, Sharbanu; Kulshymanova, Moldir; Nurgaliyev, Kanat; Issayeva, Samal; Dalibayeva, Gulshat; Bizhanova, Maira; Kulymbetova, Balzhan; Rysbekova, Karlygash; Atasheva, Arailym; Aseeva, Elena; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) refers to socially significant diseases and the improvement of diagnosis, treatment of the disease belongs to the target indicators of the State Program in Kazakhstan. Objectives: The aim of this study was to assess the demographic, clinical features, the degree of activity, damage to internal organs and therapy in patients with SLE. Methods: The study involved 89 patients with a documented diagnosis of SLE (ACR, 1997) hospitalized for inpatient treatment in rheumatology centers. The register included an assessment of gender, age, Disease Activity Index (SLEDAI 2K), organ Damage Index (DI, SLICC, 2012), and therapy. For qualitative signs, absolute and relative values (n, %) are presented. Results: In the studied cohort of patients with SLE prevailed women (98.8%), the mean age of patients was 33.610.47 years, 47% of them under 30 years old. The debut of the disease in the overwhelming majority (52%) patients is associated with stress, pregnancy and childbirth. By ethnicity: Kazakhs - 67 (75.2%), Russian - 7 (7.8%), Uighurs - 6 (6.7%), Korean - 5 (5.6%), other 5 (5.6%). 56% of patients had higher and secondary-special education. Only in a third of patients SLE was diagnosed in the first months of the disease, the rest had erroneous diagnoses, such as rheumatoid arthritis, reactive arthritis, and other systemic diseases. The disease activity (SLEDAI 2K) was very high in 9 (10.1%), high in 24 (26.9%), medium in 39 (43.9%), low in 15 (16.8%) patients and without activity were 2 (2.2%) patients. Among SLE patients, 92% with mucocutaneous manifestations, 64% had photosensitivity, 56.2% had enanthema, 77.5% had arthritis and arthralgia, 28.1% with serositis, 55% had renal involvement, 25.8% had neurological and 58.4% had hematological disorders. Irreversible organ damages (SLICC) were detected in 67.4% of patients: low DI (1 point) - 26 (29.2%), moderate (2-4 points) - 33 (37.1%) and high (> 4 points) - in 3 (3.4%) patients. Medium and high DI were observed in patients with renal and neurological involvement. Patients were predominantly in therapy: methylprednisolone (98%), cytostatics and mycophenolate mofetil (42.3%), hydroxychloroquine (39%). Biological therapy (rituximab, belimumab) was performed in patients with a high degree of activity, nephritis, and neurolupus and in 6 (6.7%) patients with good effect and the possibility of reducing glucocorticoids to minimal doses. Conclusion: Creating a register and forming a cohort allows for a more complete assessment of activity, organ damage and therapy in patients with SLE. Acknowledgement: This study was performed in the framework of the project of the Ministry of Education and Science of the Republic of Kazakhstan №AP05134328: "Development of a national registry, identification of a characteristic profile of a patient with systemic lupus erythematosus and the introduction of personalized therapy" Disclosure of Interests: None declared